ANALISIS KESALAHAN SINTAKSIS PADA KARANGAN ARGUMENTASI SISWA KELAS X SMAN 1 ADILUWIH KABUPATEN PRINGSEWU TAHUN PELAJARAN 2020/2021 - Supriyono, Supriyono; Hidayati, Ulil (STKIP PGRI Bandar Lampung, 2021)
The purpose of the study was to identify and describe sentence structure errors, phrase structure errors and clause errors in argumentative essays. The problem was raised based on the finding of syntactic errors in the argumentation essays of class X students of SMAN 1 Adiluwih, Pringsewu Regency, for the 2020/2021 academic year. The research method uses qualitative analysis with a language error analysis approach. Collecting data using the task of writing an argumentative essay. The data of this research is an argumentative essay. The data analysis uses language error analysis with the stages: marking errors, citing errors, explaining syntactic errors, both sentence, phrase, and clause errors. The results showed that the argumentative essays of class X students of SMAN 1 Adiluwih Pringsewu for the academic year 2020/2021 were found to have syntax errors. Sentence errors in the form of unstructured, inefficient, ambiguous and ambiguous sentences, piles of ideas, not unity of ideas, and inappropriate phrases and clauses. Phrase errors in the form of misordered, non-standard phrases, redundant phrases, ambiguous, plural phrases, lacking elements, misformed. Clause errors in the form of clauses as sentences, starting with conjunctions, are inefficient, ambiguous, repeating words, not having parallel meanings, and using correlative conjunctions incorrectly.